2017
DOI: 10.1159/000478082
|View full text |Cite
|
Sign up to set email alerts
|

Gonadectomy in Complete Androgen Insensitivity Syndrome: Why and When?

Abstract: Prophylactic gonadectomy has been recommended in complete androgen insensitivity syndrome (CAIS) because of an increased risk for the development of malignant germ cell tumors in the intra-abdominal gonads. No reliable screening parameters are available to detect early (pre-)malignant changes. Because the tumor risk before puberty is very low, the timing of gonadectomy has been postponed to allow spontaneous puberty and involvement of the patients in important decisions affecting their body and health. Gonadec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 28 publications
4
43
0
3
Order By: Relevance
“…In line with this observation, it has been found that only few in situ lesions progress to invasiveness in individuals who have AIS [20]. A small number of studies report a positive effect of retained gonads on bone mineral density in women with CAIS, which cannot always be obtained by hormone replacement therapy (HRT) [21, 22]. For men and women with PAIS, recommendations for the management of gonads at risk have been proposed only recently, but the evidence remains weak and partly based on extrapolations from other conditions such as testosterone biosynthesis defects [9].…”
Section: Introductionmentioning
confidence: 95%
“…In line with this observation, it has been found that only few in situ lesions progress to invasiveness in individuals who have AIS [20]. A small number of studies report a positive effect of retained gonads on bone mineral density in women with CAIS, which cannot always be obtained by hormone replacement therapy (HRT) [21, 22]. For men and women with PAIS, recommendations for the management of gonads at risk have been proposed only recently, but the evidence remains weak and partly based on extrapolations from other conditions such as testosterone biosynthesis defects [9].…”
Section: Introductionmentioning
confidence: 95%
“…In order to check the condition of the testes periodically by ultrasonography, fixation should be performed in a visible position that is easily identified in imaging test. The postponement of eventual orchiectomy to adult age is a major advantage that not only allows puberty to occur spontaneously but also permits informed and authoritative decision-making by patients [15].…”
Section: Resultsmentioning
confidence: 99%
“…Prophylactic gonadectomy has been recommended in CAIS due to increased risk of germ cell tumor during adulthood in the statement. Early gonadectomy is not necessary before onset of puberty, because CAIS has relatively low tumor risk compared with other DSDs, such as mixed gonadal dysgenesis, and no cases with tumor have been reported before onset of puberty in CAIS individuals [34,35]. Recently, surgical procedures in DSD individuals, including gonadectomy, has also been discussed in terms of ethics, which means that first-person informed consent based on ethical implications must be obtained, at least with regards to suspendable procedures.…”
Section: Discussionmentioning
confidence: 99%